2018
DOI: 10.1093/jee/tox356
|View full text |Cite
|
Sign up to set email alerts
|

Pest Prevalence and Evaluation of Community-Wide Integrated Pest Management for Reducing Cockroach Infestations and Indoor Insecticide Residues

Abstract: Pest infestations in residential buildings are common, but community-wide pest survey data are lacking. Frequent insecticide applications for controlling indoor pests leave insecticide residues and pose potential health risks to residents. In this study, a community-wide pest survey was carried out in a housing complex consisting of 258 units in 40 buildings in New Brunswick, New Jersey. It was immediately followed by implementation of an integrated pest management (IPM) program in all the cockroach-infested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…The locations were marked by taking a photo with a 1 × 1 ft wooden frame outlining the sampling spot so that future samples could be taken from the exact same locations. The sampling procedure was same as described in Zha et al (2018) [32]. A previous study shows that insecticide residue loading from floor wipe samples varies greatly in different areas of a room [33].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The locations were marked by taking a photo with a 1 × 1 ft wooden frame outlining the sampling spot so that future samples could be taken from the exact same locations. The sampling procedure was same as described in Zha et al (2018) [32]. A previous study shows that insecticide residue loading from floor wipe samples varies greatly in different areas of a room [33].…”
Section: Methodsmentioning
confidence: 99%
“…Zha et al (2018) found that after implementing a cockroach IPM program in a low-income community, insecticide residue in the kitchen floor wipe samples decreased by 90% after 7 months [32]. However, the long-term impact of IPM programs on indoor insecticide residue is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, based on pre-treatment RA 38 we chose abamectin, boric acid and thiamethoxam (mixed with λ-cyhalothrin) out of 14 registered and commercially available AIs for cockroach control. However, “over-the-counter” pyrethroid sprays and total release foggers are commonly used by residents against pests, especially cockroaches 53,54 . Our pre-treatment RA showed more than 80% survivorship when cockroaches were exposed to pyrethroid DCs (λ-cyhalothrin, β-cyfluthrin and bifenthrin) 38 , which is consistent with long-standing knowledge of kdr -type nerve insensitivity to pyrethroids known in B. germanica 34,41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Rotations thus are essential for minimizing selection pressure in the long-term. In addition, non-chemical IPM approaches that reduce reliance on insecticides would unquestionably provide added benefits 53,57 .…”
Section: Discussionmentioning
confidence: 99%
“…The concept of IPM was accepted in the fields of medicine and economic entomology (Shiff, 2002). IPM was later applied to the field of vector control (WHO, 2004;Ehler, 2006;Zha et al, 2018) and to the control of other arthropod pests, including nuisances (Mosqueira et al, 2010;Durel et al, 2015). As insecticide replacements, harmless or negligibly weakly harmful substances that act on the pests were proposed.…”
Section: Introductionmentioning
confidence: 99%